Multiple exposure : The group portrait in photography - Tonkonow, Leslie; Sollins, Susan; The Bruce Museum, Greenwich; Bayle Art Museum, Charlottesville; Oakville Galleries, Oakville, Ontario; Trachtenberg, Alan (New York : Independent Curators Inc., 1995)
Arbus, Diane ; Art Club 2000 ; Barney, Tina ; Brenner, Frédéric ; Breton, André ; Char, René ; Éluard, Paul ; Sadoul, Georges ; Burckholder ; Calle, Sophie ; Chambi, Martín ; Clark, Larry ; Clegg & Guttmann ; Coster, Gordon ; Disfarmer, Mike ; Ellis, Darrel ; Erwitt, Elliott ; Evans, Walker ; et al.
"A traveling exhibition organized and circulated by Independent Curators Incorporated, New York."
The Bruce Museum, Greenwich, May 7 to June 25 1995 ; Bayly Art Museum, Charlottesville, September 1 to October 29, 1995 ; Oakville Galleries, Oakville, January 13 to March 10, 1996.
kunstcatalogus